2022
DOI: 10.1007/s40121-021-00586-5
|View full text |Cite
|
Sign up to set email alerts
|

No Statistically Apparent Difference in Antifungal Effectiveness Observed Among Trimethoprim/Sulfamethoxazole Plus Clindamycin or Caspofungin, and Trimethoprim/Sulfamethoxazole Monotherapy in HIV-Infected Patients with Moderate to Severe Pneumocystis Pneumonia: Results of an Observational Multicenter Cohort Study

Abstract: Introduction: Pneumocystis pneumonia is a common opportunistic infection in patients with HIV/AIDS, and is a leading cause of death in this population. Early selection of effective treatment is therefore critical to reduce mortality. We conducted a clinical trial to compare the effectiveness and safety of three different antifungal treatment regimens in HIV-infected patients with moderate to severe PCP. Methods: Our study was a multicenter, observational prospective clinical trial. We recruited 320 HIV-infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The results of the OR analysis of patient gender captured from six studies [ 48 , 60 , 62 , 74 , 76 , 82 ] indicated that HIV-positive men had a 7% higher chance rate for PCP compared to women (OR:1.073; 95% CI:0.674 to 1.706; I 2 : 0%; P = 0.959)( Table 2 ). The results of standard mean difference (SMD) analysis of patient’s age captured from twenty-one studies [ 40 , 41 , 44 , 48 , 49 , 53 , 55 , 56 , 58 , 59 , 61 65 , 74 , 77 , 82 , 88 , 91 , 92 ], including 1583 PCP patients among 2044 HIV-positive cases, indicated that there is no significant difference between HIV/AIDS patients with PCP and without PCP (SMD: -0.140; 95% CI:-0.315 to -0.034; I 2 : 78.6%;P = 0.000).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the OR analysis of patient gender captured from six studies [ 48 , 60 , 62 , 74 , 76 , 82 ] indicated that HIV-positive men had a 7% higher chance rate for PCP compared to women (OR:1.073; 95% CI:0.674 to 1.706; I 2 : 0%; P = 0.959)( Table 2 ). The results of standard mean difference (SMD) analysis of patient’s age captured from twenty-one studies [ 40 , 41 , 44 , 48 , 49 , 53 , 55 , 56 , 58 , 59 , 61 65 , 74 , 77 , 82 , 88 , 91 , 92 ], including 1583 PCP patients among 2044 HIV-positive cases, indicated that there is no significant difference between HIV/AIDS patients with PCP and without PCP (SMD: -0.140; 95% CI:-0.315 to -0.034; I 2 : 78.6%;P = 0.000).…”
Section: Resultsmentioning
confidence: 99%
“…Our random effect models for SMD analysis of serum levels of CD4 + T cells [ 43 , 49 , 55 , 56 , 58 62 , 74 , 88 , 91 , 92 ], LDH [ 48 , 55 , 64 , 65 , 88 ], and BDG [ 45 , 55 , 59 , 64 , 92 ] in 12, 5, and 5 studies (respectively), indicated that serum levels of CD4 + T cells (SMD: -0.617; 95% CI:-1.122 to -0.111; I 2 : 95.1%;P = 0.000) and LDH (SMD: -0.089; 95% CI:-0.089 to 0.267; I 2 : 8.2%;P = 0.36) did not differ statistically between HIV/PCP-positive and HIV-positive PCP-negative patients. However, the mean serum and/or BAL levels of BDG of HIV/PCP-positive patients were higher than HIV-positive PCP-negatives (SMD: 2.664; 95% CI:1.110 to 4.217; I 2 : 97.7%;P = 0.000)( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…1,2 Severe cases can develop respiratory failure and even die. 3,4 It initially attracted attention among human immunodeficiency virus (HIV) patients, 5 then in solid organ transplantation recipients, haematopoietic stem cell transplantation patients, and those who received corticosteroids and chemotherapy drugs. 6 PJP often occurs in patients after solid organ transplantation such as kidney transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Pneumocystis jirovecii pneumonia (PJP), an opportunistic infection that is sometimes life‐threatening, often occurs in individuals with impaired immunity 1,2 . Severe cases can develop respiratory failure and even die 3,4 . It initially attracted attention among human immunodeficiency virus (HIV) patients, 5 then in solid organ transplantation recipients, haematopoietic stem cell transplantation patients, and those who received corticosteroids and chemotherapy drugs 6 …”
Section: Introductionmentioning
confidence: 99%
“…However, the clinical application of TMP/SMZ is associated with various side-effects [7]. One of the promising approaches to improving the therapeutic efficacy of drugs and reducing their side-effects is the loading of drugs into nanoparticles [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%